Attitudes of 200-Level Applied Science Undergraduates towards ESL Learning at Uva Wellassa University - Nayanahari, W.M.L.; Abeyweera, G.H.; Herath, H.M.D.N.; Samarasinghe, A.G.S.M.; Dissanayake, D.M.R.N.; Silva, R.R.P (University of Jaffna, 2025)
Language attitudes involve individuals’ perceptions, emotions, and beliefs about a language, shaping their motivation, proficiency, and engagement in learning and communication. The research “Attitudes of 200-Level Applied Science Undergraduates towards ESL Learning at Uva Wellassa University” aimed to identify the language attitudes of undergraduates on learning English as a Second Language and the underlying reasons behind the formation of those attitudes as their medium of study is English. A Qualitative Research design was incorporated as the methodology, and the sample consisted of 100 randomly selected students representing the four-degree programmes. Structured Interviews were conducted, and the questionnaire consisted of 25 questions that covered the three aspects: Behavioural, Cognitive and Emotional which is also referred to as the “Tripartite Model” of language attitudes by Patia Rosenberg and Carl Hoveland (1960). The Data, proportions of the attitudes and the reasons behind the formation of the attitudes were analysed using the Thematic Analytical Method. Considering the findings, 78% of the sample provided positive answers for 18 questions (72%) while 22% provided negative responses for 07 questions (28%), thus revealing the undergraduates hold positive language attitudes towards ESL. The reasons for the formation of positive attitudes were found to be motivation created due to integrative and instrumental factors, practical and goal-oriented mindset created as a result of embracing English as a tool for empowerment rather than a forced imposition. Preference for interactive and task-based learning related to Applied Science that is driven by functional multilingualism, sense of security, curriculum being relevant to their field and career, contextualized subject content which supports a decolonized approach and academic benefits that ESL creates. On the contrary, the students who provided negative responses were formed due to several reasons that are understood based on Vygotsky’s Sociocultural Theory (1978). Allocation of limited time for ESL per week, ineffective distribution of students per class has also caused negative attitudes towards ESL learning. Besides, the heavy workload in the undergraduates’ degree programmes and language difficulty, particularly in complex grammar and unfamiliar vocabulary, have paved the way for negative attitudes. To conclude, the study reveals that 200-level undergraduates in Applied Science programmes have positive attitudes towards ESL, although the identified challenges affect their learning experience. These findings can inform future ESL curriculum development and measures to alleviate the identified issues.
Keywords: Language attitudes; English as a second language; Motivation; Functional multilingualism